2017 IEEE Aerospace Conference 2017
DOI: 10.1109/aero.2017.7943601
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Kalman filters for target tracking with navigation uncertainty in one dimension

Abstract: Abstract-The vast majority of literature on target tracking assumes that the position and orientation of the tracking sensor is stationary and/or known. However, for many applications the sensor is mounted on a moving vehicle, whose motion only can be estimated with a non-negligible uncertainty. In this paper, we suggest seven possible architectures for Kalman filtering in the simplest such scenario that we can construct: Assuming that both the ownship and a single target moves along a straight line according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Given the performance of the Seapath navigation system, navigation uncertainty is of minor impact to the target tracking system, and will be neglected. This is supported by simulation studies in [23] and [3] which indicated that navigation uncertainty would have to be significantly higher to have noticeable impact. The vessel tracking and control system is implemented in the robot operating system (ROS) [19], and the vessel actuators are interfaced via a proprietary interface developed by Maritime Robotics.…”
Section: Experimental Platformmentioning
confidence: 52%
“…Given the performance of the Seapath navigation system, navigation uncertainty is of minor impact to the target tracking system, and will be neglected. This is supported by simulation studies in [23] and [3] which indicated that navigation uncertainty would have to be significantly higher to have noticeable impact. The vessel tracking and control system is implemented in the robot operating system (ROS) [19], and the vessel actuators are interfaced via a proprietary interface developed by Maritime Robotics.…”
Section: Experimental Platformmentioning
confidence: 52%
“…Sebelumnya beberapa peneliti telah menggunakan Kalman Filter pada kasus-kasus berbeda-beda seperti penurunan noise pada banyak sensor RFID secara bersamaan [5], verifikasi nilai sensor pada modul Zigbee [6] penentuan target dari suatu navigasi yang nilainya tidak menentu [7], memprediksi data pada jaringan WSN (Wireless Network Sensor) [8][9] [10]. Yang pengolahan datanya menggunakan bantuan software seperti Matlab yang artinya membutuhkan perangkat keras komputer dalam pengolahan datanya.…”
Section: Pendahuluanunclassified
“…Target tracking in the presence of navigation uncertainty has been studied for autonomous ships [6,31,32]. However, these articles have focused on a subset of the navigation space and used a radar as the tracking sensor.…”
Section: Introductionmentioning
confidence: 99%